Rare metastasis of gastric cancer to the axillary lymph node: A case report - Zhu, Qingshun; Li, Lei; Jiao, Xuguang; Xiong, Jinqiu; Zhai, Shengyong; Zhu, Guangxu; Cheng, PeiPei; Qu, Jianjun (Frontiers in Oncology, 2022)
Lymph node metastasis in patients with gastric cancer is more common, metastatic lymph nodes are often around the stomach, and metastasis is carried out in a certain order, but gastric cancer metastasis to axillary lymph nodes is very rare. Due to the small number of patients with this kind of metastasis, its clinical features and treatment are not very clear. We initially thought that the enlarged axillary lymph nodes were inflammatory lesions. Axillary lymph node biopsy was later diagnosed as gastric cancer metastases to axillary lymph nodes. The patient refused further treatment and died 11 months after the second operation because of multiple systemic metastases. We believe that metastasis of gastric cancer to axillary lymph nodes is rare and the prognosis is poor. In clinical work, the possibility of metastatic lymph nodes should be considered in patients with a history of gastric malignant tumor with enlarged axillary lymph nodes.